Fifth special issue on knowledge discovery and business intelligence - Cortez, Paulo (2020)
[extract] Artificial Intelligence (AI) is impacting our world. In the 1970s and 1980s, Expert Systems (ES) consisted of AI systems that included explicit knowledge, often represented in a symbolic form (e.g., by using the Prolog language), that was extracted from human experts.